Widerspenstige Hände Literarische Handdarstellungen und anthropologische Formationen im frühen 20. Jahrhundert - Heller, Anatol (ROMBACH WISSENSCHAFT • REIHE LITTERAE, 2022)
In literary texts of the early 20th century, the use of hands becomes a problem. The study traces the topicality of stubborn, idiosyncratic and dysfunctional hands and locates them in the media-, technology- and knowledge-historical contexts of the time. Against the background of the hand interests circulating in philosophy, medicine, anthropology and labour sciences, the 'productiveness' of the mode of representation of unruliness becomes clear. Beyond the traditional praise of human manual dexterity, moments of refusal and confusion open up a critical potential for reflection that explores new forms of possibility in the use of the hand.